Analysis of the economic impact of cystic echinococcosis in Spain - Benner, Christine (World Health Organization, 2010)
OBJECTIVE: To estimate the overall economic losses due to human and animal cystic echinococcosis (CE) in Spain in 2005. METHODS: We obtained data on annual CE incidence from surveillance and abattoir records, and on CE-related treatment and productivity losses (human and animal) from the scientific literature. Direct costs were those associated with diagnosis, surgical or chemotherapeutic treatment, medical care and hospitalization in humans, and condemnation of offal in livestock (sheep, goats, cattle and pigs). Indirect costs comprised human productivity losses and the reduction in growth, fecundity and milk production in livestock. The Latin hypercube method was used to represent the uncertainty surrounding the input parameters. FINDINGS: The overall economic loss attributable to CE in humans and animals in 2005 was estimated at 148 964 534 euros (€) (95% credible interval, CI: 21 980 446–394 012 706). Human-associated losses were estimated at €133 416 601 (95% CI: 6 658 738–379 273 434) and animal-associated losses at €15 532 242 (95% CI: 13 447 378–17 789 491). CONCLUSION: CE is a neglected zoonosis that remains a human and animal health concern for Spain. More accurate data on CE prevalence in humans (particularly undiagnosed or asymptomatic cases) and better methods to estimate productivity losses in animals are needed. CE continues to affect certain areas of Spain, despite several control initiatives since 1986. Given the high economic burden of CE, additional funding is needed to reduce human and animal infection rates through improved disease surveillance, regular treatment of dogs and greater cooperation between agencies.